Mixture of Mocaf Flour and Bamboo Flour on the Quality of Crepes Chicken Meat Based on Physicochemical and Organoleptic Characteristics - Daeng Bulang, Khusnul Khatimah Akhmad (Jurnal Ilmu dan Teknologi Peternakan Tropis, 2022)
ABSTRACTCrepes are snacks which are thin and folded like a fan. This study used mocaf flour and bamboo flour for basic ingredients of crepes. The aim of the study was to evaluate the best formula for the quality of crepes which was a mixture of mocaf flour and bamboo flour with different percentages, with the addition of 20% chicken meat in terms of physicochemical and organoleptic characteristics. The research method used a completely randomized design with 6 treatments P0 (6.5% mocaf flour: without bamboo flour), P1 (4.5% mocaf flour: 2% bamboo flour), P2 (3% mocaf flour: 3.5% bamboo flour), P3 (2.5% mocaf flour: 4% bamboo flour), P4 (1.5% mocaf flour: 5% bamboo flour), P5 (1% mocaf flour: 5.5% bamboo flour). 3 Deuteronomy. Data were analyzed using Analysis of Variance (ANOVA) and Duncan's Multiple Distance Test. The best treatment uses the Effectiveness Index method. The results show that crepes had different effects (P<0.05), on protein, fat, ash, water, carbohydrates, color L* a* b* and organoleptic (color, texture, aroma, taste), while acceptability has no effect on it. This study concludes that chicken crepes combined with 2.5% mocaf flour and 4% bamboo flour on the quality can improve the physicochemical and organoleptic characteristics. Keywords: Crepes, chicken meat, physicochemical, organoleptic